-3n(2n-5)=0

Divide each term in -3n(2n-5)=0 by -3.

-3n(2n-5)-3=0-3

Cancel the common factor.

-3n(2n-5)-3=0-3

Divide n(2n-5) by 1.

n(2n-5)=0-3

n(2n-5)=0-3

Divide 0 by -3.

n(2n-5)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

n=0

2n-5=0

Set the first factor equal to 0.

n=0

Set the next factor equal to 0.

2n-5=0

Add 5 to both sides of the equation.

2n=5

Divide each term by 2 and simplify.

Divide each term in 2n=5 by 2.

2n2=52

Cancel the common factor of 2.

Cancel the common factor.

2n2=52

Divide n by 1.

n=52

n=52

n=52

n=52

The final solution is all the values that make -3n(2n-5)-3=0-3 true.

n=0,52

The result can be shown in multiple forms.

Exact Form:

n=0,52

Decimal Form:

n=0,2.5

Mixed Number Form:

n=0,212

Solve for n -3n(2n-5)=0